Upaya Peningkatkan Prestasi Belajar Matematika Materi Penjumlahan dan Pengurangan dengan Media Tangga Pintar Siswa Kelas 1 SD Negeri Kaliwareng - Firyal Zalfa Nisrina; Dian Kusumawati; Rachmat Imam Muslim (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
Based on observations of the learning outcomes of class 1 students at Kaliwareng State Elementary School, it is known that the achievement of Mathematics scores is still low. The average score obtained was 58.6, while the KKM that had to be achieved was 60. Only 11 children or 42% completed their learning scores, the learning scores obtained were very worrying. Based on the background of the problem, the problem formulation in this research is: Can the use of smart ladder media improve student achievement in learning mathematics on addition and subtraction material in class 1 of Kaliwareng State Elementary School? After conducting research using Smart Ladder media, student learning completion reached 80%. The use of smart stairs can actually improve student learning outcomes. The indicator of success, namely the percentage of students who have completed learning, has been achieved after learning actions were carried out using smart stairs. In learning, the result was an increase in scores, namely from 42% with an average score of 48 in the pre-cycle to 66% or an average score of 59 in the level of completeness, and then reaching an average score of 80.7 (93% in the level of completeness). This is because by using Smart Ladder media, students are more active in learning, and students' learning independence increases. So that students' absorption capacity also increases.